Reach, Recruitment, Dose, and Intervention Fidelity of the GoActive School-Based Physical Activity Intervention in the UK: A Mixed-Methods Process Evaluation - Stephanie T. Jong; Caroline H. D. Croxson; Campbell Foubister; Helen Elizabeth Brown; Cornelia Guell; Emma R. Lawlor; Emma K. Wells; Paul O. Wilkinson; Edward C. F. Wilson; Esther M. F. van Sluijs; Kirsten Corder (MDPI AG, 2020)
School-based multi-component physical activity (PA) promotion is advocated; however, research has indicated that a multi-component approach may not always be effective at increasing adolescent PA. Evaluation of the GoActive 12-week multi-component school-based intervention showed no effect on adolescent PA. A mixed-methods process evaluation was embedded to facilitate greater understanding of the results, to elicit subgroup perceptions, and to provide insight into contextual factors influencing intervention implementation. This paper presents the reach, recruitment, dose, and fidelity of GoActive, and identifies challenges to implementation. The process evaluation employed questionnaires (1543 Year 9s), individual interviews (16 Year 9s; 7 facilitators; 9 contact teachers), focus groups (48 Year 9s; 58 mentors), alongside GoActive website analytics and researcher observations. GoActive sessions reached 39.4% of Year 9s. Intervention satisfaction was relatively high for mentors (87.3%) and facilitators (85.7%), but lower for Year 9s (59.5%) and teachers (50%). Intervention fidelity was mixed within and between schools. Mentorship was the most implemented component. Factors potentially contributing to low implementation included ambiguity of the roles subgroups played within intervention delivery, Year 9 engagement, institutional support, and further school-level constraints. Multiple challenges and varying contextual considerations hindered the implementation of GoActive in multiple school sites. Methods to overcome contextual challenges to implementation warrant in-depth consideration and innovative approaches.